1962
DOI: 10.2134/agronj1962.00021962005400040022x
|View full text |Cite
|
Sign up to set email alerts
|

Seedling Emergence Rate of Fall‐sown Wheat and Its Association with Plant Height and Coleoptile Length1

Abstract: Synopsis Significant differences in the emergence rate index (E.R.I.) were observed for a group of standard height and semidwarf selections as well as for groups of club and common semidwarf selections. Indexes were found to correlate positively with matureplant heights and coleoptile lengths of seedlings grown at 50° and 90° F. Partial correlations indicated that associations between E.R.I. and plant height and E.R.I. and coleoptile length were closely related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

1976
1976
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 3 publications
1
35
1
Order By: Relevance
“…These results suggest that varietal differences in response to flooding treatment are not related to emergence of seedling in the field. Although varietal differences in the germination of wheat seeds have been reported (Allan et al, 1962;Sunderman, 1964;Lafond and Baker, 1986a), we did not find any significant correlation among wheat varieties with respect to field emergence (Table I). Since the number of emerged plants depended on the seed size and their harvest year (Fig.…”
Section: Discussioncontrasting
confidence: 63%
“…These results suggest that varietal differences in response to flooding treatment are not related to emergence of seedling in the field. Although varietal differences in the germination of wheat seeds have been reported (Allan et al, 1962;Sunderman, 1964;Lafond and Baker, 1986a), we did not find any significant correlation among wheat varieties with respect to field emergence (Table I). Since the number of emerged plants depended on the seed size and their harvest year (Fig.…”
Section: Discussioncontrasting
confidence: 63%
“…These GA-insensitive dwarfing genes have a pleiotropic effect on plant growth, causing reduction in coleoptile length and seedling leaf area (Allan et al, 1962;Whan, 1976). In this study, both the first leaf length and coleoptile length in Huaai 01 were insensitive to exogenous GA 3 treatment (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Due to this association, studies conducted in wheat on the relationselection for short culm often led to a ship between coleoptile length and culm reduction of coleoptile length and, as a length, this problem still remains largefy consequence; to a reduction' of seedling unexplored in barley. Verma et al (1972) vigor and percent emergence (Livers 1958; have found that coleoptile length in barley is Allan et al 1962;Sunderman 1964; Burleigh under the control of a polygenic system with et al 1965;Feather et al 1968; Kaufmann dominance of the alleles which increase the 1968). The possibility of selecting character: therefore an analogy seems to genotypes with short culm and long or exist to the genetic control of culm length fast-growing coleoptile has, however, been (Ceccarelli et al 1974;Lorenzetti and can.J.ptanrScr.60:6E7-693(Apr.…”
mentioning
confidence: 99%